Upaya Peningkatan Pemahaman Materi Asmaul Husna Pelajaran Akidah Akhlak Melalui Penggunaan Model Pembelajaran Problem-Based Learning Pada Siswa Kelas X MA Yasni - Hidayat, Wahyuni; Rani, Neng; Supyan, Aceng; Halim, Abdul; Mubarok, Dasep Hanan (Universitas Pakuan, 2025)
EFFORTS TO INCREASE UNDERSTANDING OF ASMAUL HUSNA MATERIAL FOR MORAL FAITH LESSONS THROUGH THE USE OF PROBLEM-BASED LEARNING MODEL IN CLASS X STUDENTS OF MA YASNIThis study aims to determine the increase in understanding of the Asmaul Husna material in the subject of aqidah and akhlak through the use of the Problem Based Learning learning model in class X students of MA Yasni. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. The subjects of the study were class X students of MA Yasni. Data were collected through tests and observations then analyzed using descriptive statistics. Indicators of success are determined based on the increase in learning completeness. This study found that the application of the Problem-Based Learning (PBL) method in learning Asmaul Husna increased the effectiveness of learning. The implementation of learning increased from 80% (Cycle I) to 96% (Cycle II), student activity increased from 84.55 to 93.03, and learning outcomes increased from an average value of 74.78 (60.87% completeness) to 84.13 (91.30% completeness). This increase was influenced by improvements in strategies, such as group discussions, ice breaking, and learning media. A comparison of the two cycles shows that the PBL method is effective in increasing student involvement and understanding. The researchers concluded that the Problem-Based Learning (PBL) method was proven to increase the effectiveness of Asmaul Husna learning, with increased student involvement, learning processes, and learning outcomes from Cycle I to Cycle II.